Effect of Lecture versus Jigsaw Teaching Strategies on Maternity Nursing Students’ Attitudes and Academic Achievement - Randa Mohamed Abobaker; Kamlah Ahmed AL-Olimat; Amal Mohamed AlRuwaili; Magda Mubarak Merghani (Research Highlights in Disease and Health Research Vol. 4, 2023)
Introduction: The teaching-learning process is actively engaged in by maternity nursing students through the cooperative learning method known as "jigsaw learning." It also enables them to interact and participate in maternity nursing courses. The study’s objective was to compare the att maternity nursing students’ attitudes and academic performance in lecture and jigsaw teaching methods. Research Design: A quasi-experimental study design was used. Research Setting: The study was conducted at the Technical Institute of Nursing, Kafer El-Sheikh Governorate, Egypt, during the course entitled "Maternity Nursing." Sampling: A convenience sample of nursing students in the 3rd level and 2nd years was recruited. Number = 160 was categorized into two groups: control group (80) "lecture group" and study group (80) "jigsaw group". Tools: The data was gathered using four tools: 1. self-administered questionnaire, 2. student’s knowledge assessment tool (pre-posttest), 3. Likert attitude scale to assess the student’s attitude toward the teaching strategy, 4. Students’ Opinion Sheet. Results: There Both groups had a significant difference in the student’s achievement (post and follow-up written exams). The students’ theoretical achievement in maternity nursing lectures was higher in the study groups than in the control group on the post and follow-up exams. Students in the study group exhibited a more positive attitude concerning the teaching strategy than the students who were in the control group. Conclusion: Maternity nursing students’ attitudes and performance during the course are improved by using the jigsaw learning strategy. Recommendations: Use the jigsaw learning strategy as a teaching strategy in all academic nursing courses.